Prevalence of the population 'at risk' of developing colorectal cancer in Sri Lanka - Yasara Samarakoon; Nalika Gunawardena; Aloka Pathirana (College of Community Physicians of Sri Lanka, 2018)
Background: Colorectal cancer is the fourth leading cancer among men and sixth leading cancer among women in Sri Lanka. Objective: To estimate the prevalence of 'being at risk' of developing colorectal cancer among adults using a colorectal cancer risk prediction model developed and validated to the Sri Lankan setting. Methods: A community-based cross-sectional descriptive study was conducted among a representative sample of 811 adults aged 30 years and above in the districts of Colombo and Gampaha, selected using a multi-stage cluster sampling technique. The validated risk prediction model in the form of an interviewer-administered questionnaire was used to gather information. The prevalence of those 'at risk' of colorectal cancer was assessed based on a validated cut-off score, and those 'at risk' were further divided as 'moderate' and 'high risk' based on cut-off values agreed upon by the experts. Results: The age-adjusted prevalence of those 'at risk' was 12.5% (95% CI=12.3, 12.7). Age-adjusted prevalence of those at 'moderate' and 'high' risk were 11.8% (95% CI=11.6, 12.0) and 0.72% (95% CI=0.7, 0.8), respectively. Conclusions: The high prevalence of being 'at risk' of colorectal cancer indicates the necessity of screening for colorectal cancer as a programme in Sri Lanka. Considering the logistic difficulties in offering follow-up diagnostic colonoscopy examinations for all, the study recommends that those found as 'high-risk' be referred for colonoscopy.